FERTILITAS REMAJA DI INDONESIA: HUBUNGAN ANTARA MELAHIRKAN PADA USIA REMAJA DAN CAPAIAN PENDIDIKAN WANITA - Ari Purbowati (Research Centre for Population, Indonesian Institute of Sciences, 2019)
Adolescent fertility has become concerns at both national and international levels. The government of Indonesia views pregnancy and teenage childbearing as a problem that must be overcome. Giving birth in adolescence can lead to low levels of education. The aim of this study is to examine the relationship between adolescent fertility which is teenage childbearing and women’s educational attainment in Indonesia. The data source used is the Indonesia Demographic and Health Survey (IDHS) 2017. Based on IDHS 2017, among women who have given birth. Around 31.5% of women gave birth for the first time before the age of 20. Of those, 3.8% gave birth out of wedlock, and 9.8% gave birth after postconception marriage. By using the instrumental variable (IV) method, the results of the study show that there is a negative association between giving birth in adolescent and women’s educational attainment. After controlling for individual and community/environmental characteristics, women who experienced first birth during their adolescence have 3.5 years of education lower than women who give birth for the first time at the age of 20 years and above.